PENGARUH APLIKASI E-LKPD DAN MINAT BELAJAR TERHADAP PENINGKATAN HASIL BELAJAR MATA PELAJARAN ISMUBA SISWA KELAS 4 SD MUHAMMADIYAH 5 JAKARTA - Jihan Hasanati; Ahmad Suryadi (Jurnal Pendidikan UNIGA, 2026)
This study aims to examine the effect of using E-LKPD based on Liveworksheet and Wizer.me, as well as students’ learning interest, on learning outcomes in the ISMUBA subject, and the interaction between the two. The research employed a quantitative experimental method with a 2×2 factorial design involving 40 fourth-grade students at Muhammadiyah 5 Elementary School Jakarta. Data were collected through learning outcome tests and learning interest questionnaires, and analyzed using Two-Way ANOVA at a 0.05 significance level. The results showed a significant difference between the use of Liveworksheet and Wizer.me (F = 69.690; Sig. = 0.000), with mean scores of 81.67 and 61.67, respectively. Learning interest also had a significant effect (F = 9.234; Sig. = 0.003), but no interaction was found between media type and learning interest (F = 0.188; Sig. = 0.740). Based on these findings, it can be concluded that Liveworksheet is more effective in improving ISMUBA learning outcomes compared to Wizer.me, for both high- and low-interest students. This interactive digital media has the potential to enhance the quality of ISMUBA learning in Muhammadiyah schools.